2005
DOI: 10.7202/705009ar
|View full text |Cite
|
Sign up to set email alerts
|

Hyphomycètes aquatiques : importance dans la décomposition des litières

Abstract: Les auteurs comparent les communautés d'hyphomycètes aquatiques récoltés dans l'écume de 7 cours d'eau du Béarn et des Landes. L'abondance de spores observées dans les deux régions diffère considérablement (174-1175 spores/µl en Béarn et 2-57 spores/µl dans les Landes) tandis que les variations de richesse spécifique apparaissent faibles. L'influence de la végétation riveraine et du pH de l'eau est discutée.Des expériences de dégradation in vitro montrent que des souches isolées de Tetracladium marchalianum, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…It has been shown that aquatic hyphomycetes colonize preferentially oxygen rich waters (CHAUVET, 1992) and turbulence stimulates spore release. Thus, the use of fine mesh bags to assess the fungal assemblage structure can be questionable since a fine mesh might unnaturally reduce physical leaf fragmentation and change water flow patterns (SUBERKROPP, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that aquatic hyphomycetes colonize preferentially oxygen rich waters (CHAUVET, 1992) and turbulence stimulates spore release. Thus, the use of fine mesh bags to assess the fungal assemblage structure can be questionable since a fine mesh might unnaturally reduce physical leaf fragmentation and change water flow patterns (SUBERKROPP, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen-rich waters, characterized by high water turbulence, such as in the headwater stream sections, are suitable places for hyphomycete conidial production (CHAUVET, 1992). Water flow may transport conidia from a few hundred meters to a few kilometres along stream reaches and constitutes the most important vector for the transport of microbial cells (THOMAS et al, 1990).…”
Section: Introductionmentioning
confidence: 99%